Proses Penelitian, Masalah, Variabel dan Paradigma Penelitian - Nikmatur Ridha (Hikmah, 2017)
The study is essentially an activity or a systematic process to solve problems is performed by applying scientific methods. The purpose of all scientific endeavor is to explain, predict and control the phenomenon. The research objective is the formulation of a sentence indicates the result, something that obtained after completion of research studies, something that will be achieved / addressed in a study.